Perfil fenotípico e funcional de neutrófilos em paciente COVID-19 após vacinação - Oliveira, Yrna Lorena Matos de (2024)
Introduction: A dysregulation in the innate immune response against the SARS-CoV-2 coronavirus may contribute to a worse prognosis in COVID-19. Serum biomarkers released by neutrophils such as the TREM-1 receptor and IL-6 are associated with the severity of inflammatory diseases. Different functional profiles of neutrophils have been described with an important role in antiviral defense and also in the inflammatory process triggered by the virus. With the advance of vaccination, it is important to understand how neutrophils are contributing to the pathogenesis of the disease. Aim: To evaluate the neutrophil profile in COVID1-9 after vaccination. Methods: This study was divided into two chapters, the first referring to a meta- analysis and the second to an experimental study. The meta-analysis was carried out in order to evaluate serum levels of the soluble form of TREM-1 (sTREM-1) in humans with viral pneumonia compared to healthy controls, according to the PRISMA guideline, and seven studies were included, four studies analyzed patients with COVID-19 and three studies evaluated other viruses. The cross-sectional study was carried out with severe COVID-19 patients, 17 unvaccinated and 12 vaccinated, admitted to intensive care units. The phenotypic and functional profile of neutrophils and the dosage of serum proteins and cytokines were evaluated. The neutrophil phenotype was determined by flow cytometry using the following surface markers: CD11b (cell adhesion), CD16 (phagocytic capacity), CD182 (chemotaxis), TREM-1 (activation), HLA-DR (antigen presentation) and CD274 (suppressive activity), together with the dosage of serum proteins, IL-6 and sTREM-1 assessed using specific immunoassays and, the dosage of cytokines : GM-CSF; IFN-γ; IL-1β; IL-2; IL-4; IL-5; IL-12 p70; IL-13; IL-18; and TNF-α by the LUMINEX method. Results: The meta-analysis found increased sTREM-1 levels in COVID-19 patients compared to healthy controls (SMD 1.53; 95% CI 0.53-2.52). In addition, higher sTREM-1 levels were found in vaccinated severe COVID-19 patients compared to healthy patients. There was no significant difference between severe and non-severe COVID-19 patients. The cross-sectional study found that serum IL-6 levels were significantly higher in unvaccinated severe COVID-19 patients compared to the vaccinated group. In vaccinated patients, neutrophils expressed more surface markers TREM- 1, CD182, HLA-DR, MFI of HLA-DR and PD-L1, as well as an increase in the CD16+CD182+TREM-1+ population (p=0.0009) and the HLA-DR+PDL-1+ population (p<0.0001). Correspondingly, vaccinated patients showed significant correlations mainly related to the number of PD-L1+ neutrophils and inflammatory cytokines, while in unvaccinated patients, inflammatory cytokines were negatively correlated with TREM-1 on the surface of neutrophils. Conclusion: From these data we can conclude that the TREM-1 molecule participates in the pathogenesis of COVID-19 and that vaccination has favored a more activated state or a more prepared immune system, in terms of regulation, antigen presentation, chemotaxis, inflammatory response and immune activation in the face of SARS-CoV-2 infection.